간호대학 학생에게서 경험적 의사소통협동학습이 자아존중감 및 대인관계 변화에 미치는 효과 - 신미경; Mee Kyung Shin; 박복남; Boc Nam Park (의료커뮤니케이션, 2017)
Purpose: This study investigated the effects of a collaborative study method utilizing a communication skill on the self-esteem and interpersonal relationship ability in nursing college students. Methods: The subjects were a total of 47 university students majoring in nursing. The instruments of self respect and interpersonal relationship ability were used at the beginning, 8 th weeks after and at the conclusion of the training period. This study is based on an experiment on a subject of a single group for 15 weeks in order to identify the effects of a collaborative study method utilizing a communication skill used by nursing students. Results: The average of the total score for self respect was increased by 0.14 after 15 weeks but were not statistically significant(t=-1.97, p=.056). The average of the total score for interpersonal relationship ability increased by 0.09 on the period of after 8weeks to 15 weeks and by 0.13 on the period of beginning to 15 weeks(t=-2.29, p=.027; t=-2.67, p=.010). However repeated measure using ANOVA of the interpersonal relationship ability revealed a non-significant effect(F=.31, p=.736). Conclusion: The collaborative study method utilizing a communication skill need an almost 15 weeks to change the interpersonal relationship ability and should be used continuously.